Tingkat Berpikir Kreatif Siswa dalam Pemecahan dan Pengajuan Masalah Matematika melalui Tipe Soal Open Ended di SMP - Rahmawati Rahmawati; Rahmah Johar; Hajidin Hajidin (Jurnal Peluang, 2019)
Every individual basically has the creative potential and creative thinking abilities of students can be improved, so that the teacher needs to know the level of creative thinking abilities of the students in solving mathematical problems and filed. By knowing the level of creative thinking abilities of students the teacher can design methods, strategies and learning techniques to improve students' ability to think creatively. One way to determine the level of students' creative thinking among others, by asking students to solve problems and propose open (open ended). The use of open-ended questions can stimulate creative thinking, original thinking skills, and innovation in mathematics. This study aims to determine the level of students' creative thinking in mathematical problem solving and problem posing through open ended type of questions and the level of creative thinking of students in the filing of mathematical problems through open ended type of questions. This research is a descriptive qualitative data collection using the test method open ended questions and interviews. The subjects were students of class VII MTsN Meureudu. All the study subjects given a test with open-ended questions, the results were analyzed based on three components, namely creative thinking fluency, flexibility and originality, then researchers conducted interviews with six students to confirm an answer and describe the level of creative thinking. The results showed that two students are at level 4 (very creative), a student is at level 3 (creative), and two students are on the 2nd level (quite creative). While the other students do not have the ability to think creatively in solving problems. Three of the six students are on the 2nd level (quite creative), while three other students do not have the ability to think creatively in a posing problem.